Pemanfaatan Teknologi dan Media Pembelajaran Kreatif untuk Meningkatkan Motivasi dan Prestasi Belajar Siswa Sekolah Dasar - Fitria Nurul Aulia; Sitti Areni; Susilo Bambang Yudhiono (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The industrial revolution 4.0 has driven technological change, which drives the world of education. The integration of technology in the learning process is currently a very important aspect and needs to be considered in order to improve the quality and facilitate the learning experience. Utilizing technology-based learning media in delivering material is one effective way to achieve this. This kind of media can increase the effectiveness and efficiency of learning, and includes various formats, such as audio, visual, and audio-visual, which can be applied to various types of learning materials. Therefore, teachers must continue to innovate when choosing learning media so that students are more interested and motivated to learn. Ultimately, this has an impact on student learning. This study was conducted to assess the effectiveness of the use of technology-based learning media in elementary school environments. The use of the document review method was used; data was collected through recording and analyzing research articles on the use of technology-based media in elementary schools. The Publish or Perish application was used to retrieve data from the Google Scholar database. The analysis shows that the use of technology-based learning media has a significant influence on students' desire to learn and their level of success in learning in elementary school.